Government debt: the impact of fiscal rules at the European and national level - Kraemer Robert; Lehtimaki Jonne (Springer, 2025)
As Europe and the world surface from the pandemic of 2020-2021, public debt levels have risen substantially, the review of the European Union (EU) economic governance framework is underway and the general escape clause of the stability and growth pact (SGP) is planned to be deactivated at the end of 2023. Against this background, it is important to better understand the dynamics of public debt in the EU. This paper studies how European institutions and sectoral national fiscal rules have affected the formation of public debt. The results suggest that over the last 25 years, the SGP has been an effective tool for lowering government debt levels, at least on average. The establishment of the SGP has been the most effective at lowering government debt, while reforms of the SGP have only had limited effects. The effects of national fiscal rules are heterogenous across different rules and public sector classifications, but it seems that national fiscal rules have at least some effects beyond the SGP in all studied cases. This implies that the EU fiscal framework and EU-level fiscal policies should take into account potential interactions with national fiscal rules and both can be used to increase the effectiveness of fiscal policymaking.